Job satisfaction: Its mediating role in the effect of transformational leadership and organizational culture on employee performance - Santya, I Made Maha Dwija; Dewi, I Gusti Ayu Manuati (International research journal of management, IT and social sciences, 2022)
Employee performance is the foundation of a company, because the company's progress is the collective effort of all its employees. The purpose of this study is to analyze the effect of transformational leadership, organizational culture, and job satisfaction on employee performance and the role of job satisfaction in mediating the effect of transformational leadership and organizational culture on employee performance. The population of this study are all employees actively working at PT Sinar Nusrapress Utama in Bali Province. The sample size was 157 employee determined by saturated sampling. The data were collected through questionnaires and analyzed by using Variance-Based Structural Equation Modelling, namely Partial Least Square. The results show that transformational leadership has a positive and significant effect on employee performance, organizational culture has a positive and significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance. Job satisfaction is able to mediate the effect of transformational leadership style and organizational culture on employee performance. For PT Sinar Nusrapress Utama, this research can be used as a reference that transformational leadership style, organizational culture, and job satisfaction are important to maintain company performance and progress.